Northeast Pacific shark biology, research and conservation. - Larson, Shawn E. (Shawn Elizabeth); Lowry, Dayv (Advances in marine biology, 2017)
Northeast Pacific Shark Biology, Research and Conservation, Part B, Volume 78, the latest release in the Advances in Marine Biology series contains updated chapters that focus on a variety of topics, including, but not limited to, an Introduction to Northeast Pacific shark biology, ecology, and conservation, Shark Interactions with Directed and Incidental Fisheries in the Northeast Pacific Ocean: historic and current encounters and challenges for shark conservation, An Introduction to modeling abundance and demographic parameters in shark populations, and Sharks in Captivity: The Role of Husbandry, Breeding, Education and Citizen Science in Shark Conservation. Specialty areas in this longstanding series include marine science, both applied and basic, a wide range of topical areas from all areas of marine ecology, oceanography, fisheries management and molecular biology, and the full range of geographic areas from polar seas, to tropical coral reefs are included making this an ideal reference and resource for postgraduates and researchers in a variety of fields.